The most common problems connected with diagnostics and therapy of rheumatic diseases in family doctors practice - Zimmermann-Górska, Irena (Przewodnik Lekarza/Guide for GPs, 2011)
Actual recommendations and criteria of the most frequent rheumatic diseases – rheumatoid arthritis, spondyloarthropathies and gout as well as their treatment are presented. At the same time some problems connected with laboratory diagnostics (antistreptolysin 0 and antinuclear antibodies) are discussed.